Pengaruh Green Product Innovation Dan Green Process Innovation Terhadap Green Competitive Advantage (Studi Pada PT. Samcro Hyosung Adilestari) - Elisabeth Christian; Lutfi Alhazami (Pusat Riset dan Inovasi Nasional, 2023)
Industry is a major problem in environmental pollution that has affected the earth for decades. Inorganic waste such as hazardous waste and toxic materials contribute to environmental pollution. Indonesia produces 60 million tons of hazardous and toxic waste in 2021. This study aims to determine the effect of Green Product Innovation and Green Process Innovation on Green Competitive Advantage at PT Samcro Hyosung Adilestari. The method used in this study uses a quantitative associative approach with a total sample of 78 respondents. The instrument used is a questionnaire. Validity and reliability tests are part of testing the quality of the instrument in this study. Data were analyzed by descriptive and correlation analysis and multiple linear regression analysis was used to test the hypothesis. The results of the study indicate that there is an effect of Green Product Innovation on Green Competitive Advantage and Green Process Innovation has no effect on Green Competitive Advantage..